2015
DOI: 10.4103/0972-0707.159746
|View full text |Cite
|
Sign up to set email alerts
|

Sealing ability of three root-end filling materials prepared using an erbium: Yttrium aluminium garnet laser and endosonic tip evaluated by confocal laser scanning microscopy

Abstract: Aims:(1) To compare the sealing ability of mineral trioxide aggregate (MTA), Biodentine, and Chitra-calcium phosphate cement (CPC) when used as root-end filling, evaluated under confocal laser scanning microscope using Rhodamine B dye. (2) To evaluate effect of ultrasonic retroprep tip and an erbium:yttrium aluminium garnet (Er:YAG) laser on the integrity of three different root-end filling materials.Materials and Methods:The root canals of 80 extracted teeth were instrumented and obturated with gutta-percha. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
(10 reference statements)
1
16
2
3
Order By: Relevance
“…Le Goff et al compared the bactericidal action of the CO 2 LASER on animal teeth infected with Actinomyces odontolyticus, with that of NaOCl. [2] Results indicated an average 85% decrease in the colonyforming units in the laser-treated group, compared with the control group. However, the NaOCl treatment was statistically superior to the CO 2 laser treatment.…”
Section: Lasers In Disinfection Of Root Canal Systemmentioning
confidence: 99%
See 4 more Smart Citations
“…Le Goff et al compared the bactericidal action of the CO 2 LASER on animal teeth infected with Actinomyces odontolyticus, with that of NaOCl. [2] Results indicated an average 85% decrease in the colonyforming units in the laser-treated group, compared with the control group. However, the NaOCl treatment was statistically superior to the CO 2 laser treatment.…”
Section: Lasers In Disinfection Of Root Canal Systemmentioning
confidence: 99%
“…Gutkencht et al determined the bactericidal effect of the Ho:YAG laser on root canals in vitro and found that it was very efficient. [2] Klinke et al evaluated the bactericidal effects of Nd:YAG laser irradiation in different thicknesses of root canal dentine and found highly significant elimination of bacteria for all thicknesses. Gordon et al investigated the ability of an Er,Cr:YSGG laser with radial emitting tips to disinfect Enterococcus faecalis-infected dentine.…”
Section: Lasers In Disinfection Of Root Canal Systemmentioning
confidence: 99%
See 3 more Smart Citations